Apresentação - Pereira Filho, Antonio José; Lima Santos, Laura Daniele; Dias Ribeiro, Renata (Prometheus - Journal of Philosophy., 2025)
Apresentação do dossiê Fascismos. Psicologia das Massas. Democracia.